(untitled) (The Review of Diabetic Studies, 2024)
Background: Emergency departments (EDs) operate as high-acuity environments managing diverse acute presentations amid rising demands from aging populations and chronic diseases, leading to crowding, prolonged waits, and heightened nursing workloads that compromise patient safety through delays and errors. Nursing practice has evolved into a specialized field emphasizing triage, resuscitation, monitoring, and evidence-based protocols like HIRAID to optimize outcomes in resource-constrained settings. This review synthesizes fragmented evidence on emergency nursing roles, competencies, and barriers to evidence-based practice (EBP) adoption, addressing gaps in linking interventions to mortality, throughput, and system efficiency.​ Methods: A narrative synthesis of peer-reviewed literature was conducted, drawing from databases like PubMed and Cochrane to consolidate studies on ED nursing across triage, protocols, outcomes, and innovations up to 2025. Inclusion focused on empirical evidence evaluating nurse-led assessments, EBP frameworks, barriers/facilitators, and impacts on clinical metrics, with quasi-experimental, cohort, and RCT data informing holistic integrations of clinical and organizational factors.​ Results: Structured tools like ESI and NEWS enhance triage accuracy and deterioration detection, reducing mortality risks and lengths of stay, while nurse-initiated protocols for sepsis, pain, and stroke yield 10-14% outcome improvements. Advanced roles, digital tools, and simulations boost throughput, satisfaction, and adherence, though crowding, staffing shortages, and knowledge gaps impede EBP, with skill mix optimizing efficiency.​ Conclusions: Strengthening EBP through training, leadership, and technology can mitigate barriers, enhancing patient safety and ED performance; future research should prioritize scalable strategies for diverse contexts.​